Factors Related to Carpal Tunnel Syndrome (CTS) Complaints on Employees in the Bank BNI Branch of Palu (Jurnal Ilmu Kesehatan Masyarakat, 2020)
Carpal Tunnel Syndrome (CTS) is a disorder that occurs due to carpal tunnel or a gap in the lower hand to the wrist narrowing. The National Health Interview Study (NHIS) estimates that the reported prevalence of CTS among the adult population is 1.55% (2.6 million). This research was conducted at BNI Branch Bank Palu. The research objective is to determine the factors associated with complaints of Carpal Tunnel Syndrome (CTS) on employees at BNI Branch Bank Palu. The type of research used is quantitative using a cross-sectional approach. The number of samples was 109 people. Data were analyzed using the chi-square test at the level of confidence (ρ <0.05). The results showed that there was a relationship between years of service (ρ = 0.005), length of work (ρ = 0,000), repetitive movements (ρ = 0.001) and gender (ρ = 0.006) with complaints of Carpal Tunnel Syndrome (CTS) on employees at the Bank BNI Palu Branch. It is recommended to employees of Bank BNI Branch Palu to do muscle stretches such as moving the fingers, reducing the emphasis on the carpal tunnel, to avoid the danger of disturbances originating from repetitive and monotonous movements in the long term.